Endowment Funds as an Effective Form of Partnership between the Business Sector and the Higher Education System. Case of Training Specialists in the Tourism Industry - KHUSAINOVA, Zhibek; ASANOVA, Maral; MARDANOVA, Aliya; AKYBAYEVA, Gulvira; ABAUOVA, Gulzhan (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
To systematize theoretical, methodological and practical aspects of endowment funding as an effective form of partnership between the business sector and the higher education system (as the example of training specialists in the tourism industry) and to identify its modern country-specific features and opportunities for extrapolation and adaptation of positive foreign experience in this field in countries with developing market economies (particularly, in Kazakhstan), to ensure a sustainable social and economic growth. The work applies an arsenal of systematic, structural, statistical and comparative methods of analysis. We have revealed the economic nature of educational fundraising and its socio-economic purpose; structured the classic elements of educational fundraising and proved the endowment-funding model can be an effective form of educational fundraising; performed a country-by-country analysis of the principles of university endowment, their common features, peculiarities, and extrapolation opportunities for countries with developing market economies (particularly, for Kazakhstan).